Relationship between organizational justice dimensions and employee outcomes : the mediation role of power distance - Rashidah, Abdullah. (Universiti Malaysia Sarawak (UNIMAS), 2008)
This study was conducted to examine the mediating effect of power distance in the relationship between the organizational justice and employee outcomes (i.e., job satisfaction and job turnover). A survey research method was used to gather 164 usable questionnaires from employees who have worked in Pejabat Setiausaha Kerajaan (SUK) Negeri Selangor. Two hypotheses were developed based on the group-value model and social exchange theories. The outcomes of testing mediating model using a stepwise regression analysis showed two major findings: (l) high power distance had positively affect the relationship between procedural justice and employee outcomes (i.e., job satisfaction and job turnover) and (2) low power distance had positively affect the relationship between distributive justice and employee outcomes (i.e., job satisfaction and job turnover). This result confirms that power distance does act as a full meditating variable in those relationships. In addition, the implications of this study to organizational justice theory, methodological and practitioners, the limitations of the study and directions for future research are also discuss